Diurnal temperature range: A climatological primer for health researchers - Robert Davis; Grace Delaar; Kaleb Notari; Mia McCarrick; Parker Sims; Jane Ruggles; Julia Cardwell; Charles Konrad; Chris Fuhrmann (PLoS ONE, 2026)
Days with high diurnal temperature range (DTR) are commonly linked to morbidity and mortality, yet these health impacts are rarely connected with the underlying meteorological factors. To provide health researchers with much-needed context, we examine the climatology of DTR in the continental United States from 1950 to 2022 using the gridded ERA5 Land reanalysis archive. DTR has declined significantly over the period of record over much of the United States, with stronger signals in the east and north in summer and autumn. Extreme positive DTR values (95th percentile), which are commonly linked to morbidity, are also declining significantly. DTR declines can be ascribed to maximum temperatures increasing at a slower rate than minima, with minimum temperatures rising in response to increasing atmospheric humidity, cloud cover, and precipitation. Given that DTR trends are clearly linked to anthropogenic warming, this would imply reduced health risks, if DTR is a direct causal exposure. Because the most extreme DTR days occur under calm, low-humidity and cloud-free conditions, clinical evidence is needed to demonstrate how and why these weather conditions produce intra-day changes in exposure that are physiologically harmful.